Internal and External Factors Affecting the Compliance of MSME Taxpayer - Andayani, Nur; Haninun, Haninun (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
This study aims to analyze internal and external factors that affect income taxpayer compliance in Micro, Small, and Medium Enterprises (MSMEs). The research variables include Tax Knowledge, Money Ethics, Tax Socialization, and Modernization of the Tax Administration System as independent variables, as well as Tax Compliance as dependent variables. The research uses a quantitative method with a survey approach. Data was collected through a questionnaire distributed to MSME taxpayers. The analysis technique used is multiple linear regression. The results of the study show that Tax Knowledge, Tax Socialization, and Modernization of Tax Administration System have a positive and significant effect on Tax Compliance. Tax knowledge provides an important foundation for taxpayers to understand their obligations. Socialization of taxation increases awareness, while modernization of the administrative system simplifies the tax process. On the contrary, Money Ethics has a negative and significant effect on Tax Compliance. A view of money ethics that is not in line with the public interest can reduce taxpayers' awareness in fulfilling tax obligations. This research highlights the importance of strengthening education and modernizing the system to improve tax compliance.